PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN KOMITMEN KARYAWAN TERHADAP KINERJA DOKTER DAN PERAWAT DI RSUD RUTENG-NTT - Rosalia Heldy Nono, Rosalia Heldy Nono (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
The Purpose of this study was to determine the effect of leadership, work motivation and employee commitment to performance and to determine the importance of leadership variables, work motivation and employee commitment to the performance of doctors and nurses at Ruteng-NTT Regional Hospital. To analyze this problem, multiple regression analysis was used using 42 samples based on purposive sampling. Purposive Sampling means that the determination of a sample that considers certain criteria that have been made against an object in accordance with the objectives of the study. The results of the study illustrate that leadership, work motivation and employee commitment variables significantly influence the performance of doctors and nurses. Based on the level of influence, in RSUD Ruteng-NTT leadership variable is the most dominant factor influencing performance, and sequentially followed by work motivation and employee commitment factors. Thus the development of leadership in the Ruteng-NTT Regional Hospital needs to be a concern..